Calcicole–calcifuge plant strategies limit restoration potential in a regional semi-arid flora - Cross, Adam; Lambers, Hans (2021)
Aim: To examine calcicole and calcifuge plant strategies, as well as nutrient-acquisition strategies, as drivers of the distribution of species in response to edaphic factors, and the degree to which these strategies may act as filters to species establishment in ecological restoration on heavily altered or reconstructed substrates.